Kyai Leadership Management Model in Improving Quality Performance of Educators and Education Personnel in Islamic Boarding Schools Ibnussabil Santan Tengah - Anggraini, Selvia; Barizi, Ahmad (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
The Kyai leadership model in Islamic boarding schools plays a major role in improving the performance of educators and education personnel. As a leader, at least he must be able to influence, motivate, protect, and guide his subordinates to have significant performance quality. Thus, optimal performance is directly proportional to the institution's success in achieving its vision, mission, and goals. This study was conducted to find out how the Kyai leadership management model is carried out at the Ibnussabil Santan Tengah Islamic Boarding School in improving the quality of performance of educators and education personnel from a philosophical perspective. The research method uses a qualitative approach by describing the leadership management model used in improving the quality of performance of educators and education personnel, in this case, interviews and documentation are the data collection techniques. The results of the study showed that there is no best leader model because all types of leadership must be used according to the situation or circumstances to improve the quality of performance of educators and education personnel effectively.   Keywords: Leadership Management Model, Performance of Educators, and Education Staff